Enhancing Firm Value Through Carbon Management Accounting System and Environmental Disclosure: A Systematic Review and Conceptual Framework on Climate Change Mitigation - Muhammad Ja’far Shodiq; Azizah Azmi Khatamy; Rita Rosalina (Jurnal Planologi, 2026)
Abstract. The current development of climate change conditions, which are worrying, encourages companies to be more responsible for their emissions and prioritize mitigation strategies to prevent climate change. This article proposes a carbon management accounting system (CMAS) model, which can be the basis for carbon emission disclosure (CED) and effectively increase firm value. This study extensively reviewed previous research and developed a new model by conducting a systematic literature review so that a conceptual framework for the relationship between CMAS, CED, and firm value could be developed. This research produces a new model finding that can contribute to environmental accounting theory. It proposes a framework that company managers can apply to take steps to mitigate climate change through managing carbon emissions. This study provides a foundation for future research to examine both models as an integrated approach to enhancing CED and overall firm value in the Indonesian industry.Keywords: Firm Value; Carbon Management Accounting System; Carbon Emission Disclosure; Climate Change